Acta Geographica Lodziensia – on the journal's 75th anniversary - Dzieduszyńska, Danuta; Forysiak, Jacek (Acta Geographica Lodziensia, 2024)
In 2023, Acta Geographica Lodziensia will celebrate its 75th anniversary. The anniversary has been taken as an op-portunity to present a historical account of how the journal’s profile has changed over the years. Particular attention was paid to the last decade, when there were changes in the pattern of editorial work. They resulted in the need to adapt the publishing sequence to the development of online communication channels, indexation requirements and the journal’s position as meas-ured by its presence in reference databases, including the SCOPUS database. Recent years have seen a shift from the dominance of monographic volumes to collective ones, with topics that go beyond the regional framework.